2004
DOI: 10.1200/jco.2004.09.154
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Yttrium-90—Labeled Anti—Prostate-Specific Membrane Antigen Monoclonal Antibody J591 for Androgen-Independent Prostate Cancer

Abstract: The recommended dose for (90)Y-J591 is 17.5 mCi/m(2). Acceptable toxicity, excellent targeting of known sites of PC metastases, and biologic activity in patients with androgen-independent PC warrant further investigation of (90)Y-J591 in the treatment of patients with PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
203
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(213 citation statements)
references
References 18 publications
6
203
2
2
Order By: Relevance
“…PSMA, also known as glutamate carboxypeptidase II or N-acetyl-L-aspartyl-L-glutamate peptidase I, is an excellent cell-surface target for prostate cancer because its expression is up-regulated throughout all stages of prostate cancer progression and is highly restricted to prostate cells, with very low levels of expression detectable in other tissues (19). Indeed, several αPSMA monoclonal antibodies have been used as vehicles for the targeted delivery of cytotoxic agents including radioactive isotopes, small molecules, and protein toxins (4,20,21). A series of small molecule PSMA inhibitors with high affinity (in the low nanomolar range) and selectivity also have been explored for selective lysis or imaging of PSMA + prostate cancer cells (18,22,23).…”
Section: Resultsmentioning
confidence: 99%
“…PSMA, also known as glutamate carboxypeptidase II or N-acetyl-L-aspartyl-L-glutamate peptidase I, is an excellent cell-surface target for prostate cancer because its expression is up-regulated throughout all stages of prostate cancer progression and is highly restricted to prostate cells, with very low levels of expression detectable in other tissues (19). Indeed, several αPSMA monoclonal antibodies have been used as vehicles for the targeted delivery of cytotoxic agents including radioactive isotopes, small molecules, and protein toxins (4,20,21). A series of small molecule PSMA inhibitors with high affinity (in the low nanomolar range) and selectivity also have been explored for selective lysis or imaging of PSMA + prostate cancer cells (18,22,23).…”
Section: Resultsmentioning
confidence: 99%
“…The details of this technique have been published in previous studies using J591 and may be found there (11).…”
Section: End Pointsmentioning
confidence: 99%
“…Previously published phase I studies of J591 have dose escalated the radioconjugate and have examined the safety and antitumor effects of increasing amounts of radiation (10,11). To develop J591 as a naked antibody, radioconjugate, or chemoconjugate, we sought to explore the effect of dose escalating the antibody mass on pharmacokinetics, biodistribution, and ADCC activation, the putative mechanism by which unlabeled antibody would mediate antitumor effects.…”
mentioning
confidence: 99%
“…[8][9][10][11] Biochemical and objective measurable disease responses were reported in some patients treated with radionuclide conjugates of a humanized MAb, J591, that binds to the extracellular domain of PSMA. [12][13][14][15][16][17][18] The safety profile of passive immunotherapy with J591 and its derivatives, along with specific localization of radionuclide-labeled MAb to tumor sites in patients with metastatic prostate cancer or other solid tumors, supports the potential clinical benefit of antibodies and T cells specific for PSMA induced by active immunization. In addition to these studies, clinical trials of active immunotherapy have been completed with no evidence of toxicity, [19][20][21][22] and some anecdotal declines in serum prostate-serum antigen (PSA) were reported.…”
mentioning
confidence: 99%